1998
DOI: 10.1364/josab.15.002763
|View full text |Cite
|
Sign up to set email alerts
|

Bandwidth study of volume holography in photorefractive InP:Fe for femtosecond pulse readout at 15 μm

Abstract: The Bragg selectivity of volume holograms makes them not well suited for many Fourier imaging processing applications in the space domain because they perform the function of a spatial filter and limit the field of view. Similarly, for femtosecond pulse holography they reduce the spectral bandwidth of the diffracted signal. However, we show both theoretically and experimentally that it is much easier in the frequency domain than in the space domain to achieve a large enough diffraction bandwidth of volume holo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 26 publications
(30 reference statements)
1
16
0
Order By: Relevance
“…Volume holographic techniques are of particular interest for their spectral sensitivity and their capacity to achieve spatial as well as temporal modulation of UPB. Recent studies [1][2][3][4] have shown that by choosing proper grating parameters based on the coupled wave theory of Kogelnik [5], it is possible to achieve a large diffraction bandwidth for the readout UPB to be used for frequency-domain pulse shaping, which is applied to the one dimension volume gratings. The input and output boundaries are much larger than the grating thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Volume holographic techniques are of particular interest for their spectral sensitivity and their capacity to achieve spatial as well as temporal modulation of UPB. Recent studies [1][2][3][4] have shown that by choosing proper grating parameters based on the coupled wave theory of Kogelnik [5], it is possible to achieve a large diffraction bandwidth for the readout UPB to be used for frequency-domain pulse shaping, which is applied to the one dimension volume gratings. The input and output boundaries are much larger than the grating thickness.…”
Section: Introductionmentioning
confidence: 99%
“…The research on diffraction of ultrashort optical pulses by VHGs has recently attracted considerable attention. Ding [9] have shown both theoretically and experimentally that it is possible in frequency domain to achieve a large enough diffraction bandwidth of VHG for a bandwidth of 100fs pulses mainly by increasing the grating period and decreasing the grating thickness. Recently Wang [10] have studied the pulse shaping properties of a VHG read by an ultrashort pulse considering the combined effects of the grating parameters, the dispersion and optical anisotropy of the media and the polarization state of the incident light.…”
Section: Introductionmentioning
confidence: 99%
“…For the even shorter pulses, in which the above method is difficult to utilize, shaping them in the Fourier domain offers an alternative technique, where the optical frequency components of the UPB are spatially dispersed by a dispersive element, then modified by a filter, and recombined by an identical dispersive element to form the temporal output with a shaped waveform. Among many filtering masks for the UPBs, volume holographic gratings (VHGs) are interesting because of their flexibility and the possibility of using them to implement dynamic processing [6][7][8][9][10][11][12] . Y. Ding [7] et al have shown both theoretically and experimentally that in the frequency domain it is possible to achieve a large enough diffraction bandwidth of VHG for the bandwidth of 100-fs pulses mainly by increasing the grating period and decreasing the grating thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Among many filtering masks for the UPBs, volume holographic gratings (VHGs) are interesting because of their flexibility and the possibility of using them to implement dynamic processing [6][7][8][9][10][11][12] . Y. Ding [7] et al have shown both theoretically and experimentally that in the frequency domain it is possible to achieve a large enough diffraction bandwidth of VHG for the bandwidth of 100-fs pulses mainly by increasing the grating period and decreasing the grating thickness. Recently the studies of S. Teng [8] have included the dispersion effect in the crystal.…”
Section: Introductionmentioning
confidence: 99%